Eficiência fotoquímica das plantas e atividade da enzima pectinametilesterase na polpa de frutos do mamoeiro (Carica papaya L.) - Fontes, Renata Venturim (2005)
This work was developed as objective to detect, by the technique of emission at the chlorophyll fluorescence, stress in mamoeiro plants of cultivates Tainung and Sunrise Solo, aiming at to improve the handling preharvest of the culture. The experiments had been lead in the field and, monthly, they had been made measured of emission at the chlorophyll fluorescence as well the text of nitrogen, match and potassium in petiole foliar and the activity of nitrate reductase in leaves. The values of amplitude of day/night temperature, maximum temperature and monthly rainfall of the region had been gotten of a metereological station at INMET in the Incaper/Linhares-ES. The presented results had allowed to conclude that high values of amplitude of day-night temperature had caused increase of the initial fluorescence and reduction of the efficiency photochemistry only in the plants of cultivate Tainung, that had also presented its photochemistry efficiency more sensible to the increase of temperature of that the plants of cultivate Sunrise Solo, that had presented its photochemistry efficiency more sensible to the rainfall variations. The nitrogen text in petiole foliar was presented higher how much bigger it was the text of match and potassium in petiole foliar in both cultivates Tainung and Sunrise Solo. The activity of the enzyme nitrate reductase increased with the nitrogen text in plants of both cultivates. The values of correlation, between photochemistry efficiency and activity of nitrate reductase, presented for cultivates them, had shown that the photochemistry efficiency in the plants of cultivate Sunrise Solo is more dependent the activity of nitrate reductase that the photochemistry efficiency of the plants of cultivate Tainung. Based in the results, it is concluded that the photochemistry efficiency of fotossistema II, gotten by means of the technique of emission at the chlorophyll fluorescence, can be used as tool to indicate stress in mamoeiro plants, aiming at to improve the handling in the preharvest of the culture.